2020
DOI: 10.1007/s43152-020-00010-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Microenvironments for Treating Glioblastoma

Abstract: Purpose of Review This review focuses on the development and progression of glioblastoma through the brain and glioma microenvironment. Specifically, we highlight how the tumor microenvironment contributes to the hallmarks of cancer in hopes of offering novel therapeutic options and tools to target. Recent Findings The hallmarks of cancer represent elements of cancer that contribute to the disease's malignancy, yet elements within the brain tumor microenvironment, such as other cellular types as well as bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Furthermore, GSCs are also known to undergo phenotypic plasticity upon exposure to treatment or other microenvironment signals. [ 51 ] To that end, in order to investigate if there was evidence of GB3‐RFP cell differentiation or plasticity, we further investigated the expression of GFAP (astrocytic and glial progenitor marker) and AQP4 (astrocyte marker). In all conditions, GB3‐RFP cells were found to be GFAP – and AQP4 – , which indicated that they were not differentiating into astrocyte lineages or demonstrating any phenotypic plasticity at least for these two markers, while astrocytes expressed GFAP and AQP4 (Figures S2 and S3a–c , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, GSCs are also known to undergo phenotypic plasticity upon exposure to treatment or other microenvironment signals. [ 51 ] To that end, in order to investigate if there was evidence of GB3‐RFP cell differentiation or plasticity, we further investigated the expression of GFAP (astrocytic and glial progenitor marker) and AQP4 (astrocyte marker). In all conditions, GB3‐RFP cells were found to be GFAP – and AQP4 – , which indicated that they were not differentiating into astrocyte lineages or demonstrating any phenotypic plasticity at least for these two markers, while astrocytes expressed GFAP and AQP4 (Figures S2 and S3a–c , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…GBM persistently communicates with its TME, and the TME contributes to the tumorigenesis and progression of GBM (reviewed in[ 79 , 80 ]). The GBM TME is extremely heterogeneous, consisting of the extracellular matrix, tumor cells such as glioma stem cells (GSCs), and non-tumor cells, including endothelial cells, pericytes, microglia, immune cells, oligodendrocytes, neurons, astrocytes and myeloid-derived suppressor cells (reviewed in[ 81 ]). Extracellular vesicles containing soluble proteins, DNA, mRNA and noncoding RNAs enable communication between the GBM and the TME, and these vesicles contribute to angiogenesis, invasion, evasion of apoptosis and resistance to drugs (reviewed in[ 82 , 83 ]).…”
Section: Gbmmentioning
confidence: 99%
“…Furthermore astrocytes and microglia contribute to a dense physical barrier protecting GBM from the infiltration of macromolecules or cells. Novel therapeutics are being developed that aim to specifically modulate the GBM microenvironment, including immunotherapy, cell-based immunotherapies, or ECM-remodeling therapeutics [ [31] , [32] , [33] , [34] , [35] , [36] ]. We found that co-culture with stromal cells increased the resistance to cytotoxicity caused by natural killer (NK) cells.…”
Section: Introductionmentioning
confidence: 99%